2008
DOI: 10.1111/j.1600-0501.2007.01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone regeneration of dental implant dehiscence defects using a cultured periosteum membrane

Abstract: This study demonstrated the feasibility of a CP membrane to regenerate bone at implant dehiscence defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Notably, no immunological reactions related to the use of allogeneic or human cells were reported in these studies. Most studies reported on the use of bone marrow mesenchymal stem cells (BMSC); three studies used periosteal cells (POC) (Mizuno et al, ; Ribeiro et al, , b), two studies used periodontal ligament stem cells (PDLSC) (Kim et al, ; Park et al, ), two studies used adipose tissue‐derived MSC (Bressan et al, ; Xu et al, ) and one study used endothelial progenitor cells (Machtei et al, ). MSC were used in early (one to six) passages, with (seven studies) or without osteogenic pre‐induction.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, no immunological reactions related to the use of allogeneic or human cells were reported in these studies. Most studies reported on the use of bone marrow mesenchymal stem cells (BMSC); three studies used periosteal cells (POC) (Mizuno et al, ; Ribeiro et al, , b), two studies used periodontal ligament stem cells (PDLSC) (Kim et al, ; Park et al, ), two studies used adipose tissue‐derived MSC (Bressan et al, ; Xu et al, ) and one study used endothelial progenitor cells (Machtei et al, ). MSC were used in early (one to six) passages, with (seven studies) or without osteogenic pre‐induction.…”
Section: Resultsmentioning
confidence: 99%
“…Although the GBR technique has been extensively studied for peri‐implant bone regeneration (Simion et al 2001, Zitzmann et al 2001, Casati et al 2002, Kim et al 2002a, b, Lima et al 2003, de Vasconcelos Gurgel et al 2007, Gurgel et al 2008), this approach has presented limitations to predictably restore bone tissue around dental implants (Buser et al 1990, Caplanis et al 1997, Schliephake et al 2000, Lima et al 2003, Botticelli et al 2004a, b). Based on the development of novel regenerative strategies using cell‐based tissue engineering, positive outcomes have been revealed, associated with the use of PCs in peri‐implant bone reconstruction (Mizuno et al 2008, Ribeiro et al 2010). Thus, the purpose of the present study was to evaluate the ability of the combined approach using PCs and GBR on bone regeneration of dehiscence‐type defects around dental implants.…”
Section: Discussionmentioning
confidence: 99%
“…The favourable results promoted by periosteal cells in this study are in line with previous investigations that have shown the potential of PCs in bone formation (Zhu et al 2006, Agata et al 2007, Yoshimura et al 2007). In this context, Mizuno et al (2008) demonstrated the feasibility of a cultured periosteum, in association with platelet‐rich plasma gel, for use in bone regeneration at sites of implant dehiscence. In addition, a recent study from our research group showed that periosteum may be an important source of osteogenic cells for tissue engineering in peri‐implant dehiscence‐type defects (Ribeiro et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…PRP has demonstrated its positive effect on bone turnover and the biological behaviour of periosteal cells in vitro as well as in vivo (Mizuno et al, 2008;Plachokova et al, 2008;Torres et al, 2009;Gassling et al, 2010). Gassling et al demonstrated in a current in vitro study an osteopromoting influence by using platelet-rich fibrin (PRF) on periosteal cells to be suitable for bone tissue appliances (Gassling et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Platelet-rich plasma (PRP), releasing high concentrations of growth factors involved in bone healing, has shown conflicting results regarding it's osteopromoting potency in the literature, whether alone or in combination with bone substitutes and target cells (Alsousou et al, 2009). However, PRP has demonstrated its positive effect on bone turnover and the biological behaviour of periosteal cells in vitro as well as in vivo (Mizuno et al, 2008;Plachokova et al, 2008;Torres et al, 2009;Gassling et al, 2010). The simple procedural technique and the absence of risk factors (transmission of diseases or autoimmune response) make PRP a reliable source of autologous growth factors in tissue engineering.…”
Section: Introductionmentioning
confidence: 97%